(untitled) (Community Based Medical Journal, 2019)
Lung cancer is the most prevalent malignant neoplasm in most of the countries, and is leading cause of mortality worldwide. Till date tobacco consumption is the main etiological factor in lung carcinogenesis. Other factors such as genetic susceptibility, poor diet, occupational exposures and air pollution may act independently. Treatment of lung cancer is time consuming, costly and need special care during its management. Post treatment complications also more and sometimes it is more serious and becomes life threatening to the patients. The study was done to find out the most common risk factors of lung cancer, for this we can take necessary preventive measure from those risk factors to prevent health burden and mortality from lung cancer.This observational study was done in the department of Medical Oncology, National Institute of Cancer Research and Hospital (NICRH), Mohakhali, Dhaka, from January 2012 to May 2012. One hundred and six (106) patients, aged over 30 years, included all sexes, were diagnosed as a lung cancer by histopathology and came for chemotherapy, were selected randomly in this study after informed written consent. In this study we found males are predominantly affected (92.45%) by lung cancer and common age groups affected are between 51-60 years (39.62%). Among the occupation farmers are more affected (77.35%) and most of them were active smokers (64.15%). In our study we found that right side of lung is more affected (58.49%) than left side and adenocarcinoma was predominant (35.84%). Control of tobacco smoking is the most important preventive measure. This study may help us to identify the etiological aspect and future preventive efforts and research be needed to focus on tobacco smoking and non-cigarette tobacco smoking products, as well as better understanding of risk factors underlying lung carcinogenesis in never-smokers. CBMJ 2019 January: vol. 08 no. 01 P: 23-29